SCiPad: Effective Implementation of Telemedicine Using iPads with Individuals with Spinal Cord Injuries, a Case Series - Shem, Kazuko; Sechrist, Samantha J.; Loomis, Eleanor; Isaac, Linda (Frontiers in Medicine, 2017)
Background: Individuals with spinal cord injury (SCI) must often travel long distances to see a rehabilitation specialist. While telemedicine for pressure ulcer management has been used in this population, real-time video telecommunication using iPad has never been described. Objective: The objective of this study was to provide specialized care for persons with SCI through telemedicine consultation expediently in order to address medical needs, manage secondary complications, and to improve quality of life (QoL) of individuals with SCI. Methods: Ten individuals with SCI participated in the telemedicine program using iPads for 6 months as a feasibility study at a single-center, county hospital. The participants contacted the project staff for SCI-related conditions and were then connected to a SCI-trained healthcare provider within 24 hours via FaceTime. Main outcome measures included healthcare utilization; QoL and psychosocial measures collected at baseline and at 6 months: Reintegration to Normal Living Index (RNLI), Life Satisfaction Index- A (LSI-A), and Patient Health Questionnaire 9 (PHQ-9); and a Program Satisfaction Survey. Results: Ten patients (7 with tetraplegia, 3 with paraplegia; 8 males and 2 females) with an average age of 34.4 (18-54) years were enrolled. The average baseline and 6 month follow-up scores were: RNLI - 77.1 ±21.7 and 78.7 ± 24.0 respectively; LSI-A - 25.4 ±7.4 and 26.4 ± 8.2 respectively; and PHQ-9 were 6.8 ±5.3 and 9.9 ± 4.9 respectively. Telemedicine encounters included topics such as pain, bladder and skin management, medication changes, and lab results. The Program Satisfaction Survey yielded positive results with 100% of program completers stating they would recommend the program and would like to continue having telemedicine. Conclusion: This is the first known successful project using iPad to provide telemedicine in the SCI population. This study discusses the implementation of such a telemedicine program in a health system including limitations. It describes the clinical viability of telemedicine using iPads in the SCI population for care beyond that of just pressure ulcer management. This project provides evidence for using a tablet device like an iPad as an effective and efficient patient management tool.